Hubungan Kadar Timah Hitam (Pb) Dalam Darah Dengan Profil Darah Studi Pada Petugas Pengujian Emisi Gas Buang Dinas Perhubungan Kabupaten Purbalingga dan Banjarnegara - Ratih Hafsari Purwindah; Sulistiyani Sulistiyani; Budiyono Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Fuel oil in Indonesia is still using of leaded gasoline, so that 70% of Pb from the burning will be emitted to the air. The official exhaust emission testing have a high risk, exposure to which continue to cause health problems, one of which is a disorder of the blood profile. The purpose of this study was to analysis the relationship between blood lead and blood profiles in exhaust emissions testing officer department of Transportation District Purbalingga and Banjarnegara. Methods : This research method was an observational analytic research with a cross sectional study design.Subjects were official exhaust emission testing with the inclusion criteria.Variables examined in this study are blood lead and blood profiles in the official exhaust emission testing. Data was collected through interviews, observation and measurement. Analysis of data using univariate analysis, bivariate analysis with spearman rank correlation. Results : The study found the average lead was 13.362 µg/dl, which means it was under the toxic threshold (40 ug/dl) and the average of blood profiles consisting of hemoglobin, erythrocytes, leukocytes, platelets, hematocrit was 15.737 ug/dl; 5.210.106/ml; 8.0723.103 / ml; 220.06.103/ml; 45.383%, 87.31 fl; 30.297pg; 34.685 fl. Bivariate analysis showed that there was a relationship between blood lead and blood profile (erythrocytes and hematocrit ), with  p-value and sequentially rho 0.018; 0.397 and 0.039; 0.35 (p-value <0.05). Conclusions : The conclusion of this study, although the value level of blood lead below the threshold toxic but are at risk in blood profile (decrease the number of erythrocytes and hematocrit levels) so that there is need for an appeal to the official testing of exhaust emissions in order to use Personal Protective Equipment (PPE) like a respirator, to reduce customs cigarette consumption, routine doing check-ups, increase the consumption of foods containing iron and vitamin C as well as expand the ventilation in the testing room, install exhaust and greenery around the testing room exhaust emissions. Keywords: blood lead, blood profiles, the official exhaust emission testing